2020
DOI: 10.1111/aogs.14014
|View full text |Cite
|
Sign up to set email alerts
|

Do high‐dose progestins impair sexual function in women treated for endometriosis? A prospective observational longitudinal study

Abstract: Introduction High‐dose progestins are used as an effective therapy for painful symptoms of endometriosis but their impact on sexual function has been poorly studied. The study aims to assess the impact of high‐dose progestin on sexual function among women treated for endometriosis. Material and methods In this bicenter prospective observational study, women with endometriosis who received medical or surgical treatment for endometriosis and who were sexually active were included. They completed the Sexual Activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The use of the minimum clinically important difference allows for a closer focus on the domain of concern for the patient and can be used to guide symptom management ( Thirlaway et al , 1996 ). Consistent with the aim of the current study to explore overall sexual function rather than limiting the scope to the experience of dyspareunia, Oppenheimer et al (2024) argue that the selected sexual function measure must account for the entire sexual response cycle and not be isolated to measurement of pain during penetration alone. While the FSFI does allow for an assessment of the full sexual response cycle, further development of endometriosis-specific scoring norms is recommended.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The use of the minimum clinically important difference allows for a closer focus on the domain of concern for the patient and can be used to guide symptom management ( Thirlaway et al , 1996 ). Consistent with the aim of the current study to explore overall sexual function rather than limiting the scope to the experience of dyspareunia, Oppenheimer et al (2024) argue that the selected sexual function measure must account for the entire sexual response cycle and not be isolated to measurement of pain during penetration alone. While the FSFI does allow for an assessment of the full sexual response cycle, further development of endometriosis-specific scoring norms is recommended.…”
Section: Discussionmentioning
confidence: 75%
“…A recent systematic review conducted by Oppenheimer et al (2024) has found that while the FSFI can be used to discriminate between endometriosis subtypes and has efficacy in evaluating outcomes associated with medical treatment, it may lack specificity for measuring surgical outcomes and low scores may not necessarily be solely reflective of the impacts of endometriosis. In contrast, the use of the Sexual Activity Questionnaire (SAQ: Thirlaway et al , 1996 ) was noted to have good responsiveness for measuring surgical outcomes in the domains of pleasure and discomfort, has been validated in an endometriosis sample, and allows for a measure of clinically important difference ( Oppenheimer et al , 2024 ). The use of the minimum clinically important difference allows for a closer focus on the domain of concern for the patient and can be used to guide symptom management ( Thirlaway et al , 1996 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unidimensionality is an interesting property for clinician use in everyday practice to monitor the effect of the treatment of endometriosis on sexual function. 88 A third questionnaire, the SHOW-Q distinguished itself by good measurement properties for "hypothesis" and "responsiveness," although it is less frequently used.…”
Section: Discussionmentioning
confidence: 99%
“…One interesting property is that it is unidimensional, 20 which facilitates the calculation and use of the score. Unidimensionality is an interesting property for clinician use in everyday practice to monitor the effect of the treatment of endometriosis on sexual function 88 …”
Section: Discussionmentioning
confidence: 99%
“…She refused oral medication after surgery, but strongly desired for pain relief and recurrence prevention. Considering high-dose progestin contributes to recurrence prevention and dysmenorrhea relief (25,26), two intrauterine devices and subdermal implants were applied after multidisciplinary consultation and the total dose of levonorgestrel (130 μg/day) was reported to be safe (27).…”
Section: Adjuvant Hormonal Therapymentioning
confidence: 99%